Automorphisms on complex simple Lie algebras of order 3: DOI: 10.48129/kjs.10668 - Hsin, Ching-I (Kuwait Journal of Science, 2022)
For complex simple Lie algebras, the article provides classification of all automorphisms of order 3. The method is an extension of Dynkin diagrams, so that the classification is a listing of diagrams which represent automorphisms of order 3. This work extends an earlier result on automorphisms of order 2. As an application, it shows that for automorphisms of orders 2 and 3 only, the invariant subalgebra determines the automorphism.